Subsídios para o planejamento e gestão dos recursos hídricos na Bacia do Rio Puraquequara - AM - Neves, Renato Kennedy Ribeiro (2018)
The Puraquequara River basin is the geographically located space unit in the eastern portion of the municipality of Manaus. Throughout contemporary history, this region was occupied by small population clusters that were spatialized in the Lower Puraquequara region, this flow of expansion, from the years 2000, extends to the Middle and Upper Puraquequara. In this basin, innumerable activities are developed such as: tourism, recreation, subsistence and sport fishing, maintenance and construction of small and large ferries, cattle slaughtering and cutting, jungle hotels, family farming and self-consumption. The recognition of these practices makes it possible to identify the main actors who directly or indirectly benefit from the region's natural resources. In this context, the research aims to generate subsidies for the Planning and Management of Water Resources in the Puraquequara River basin. For this, the study characterized the dynamics of Land Use and Occupancy, from 2005 to 2016, identified the Multiple Uses of Water and evaluated physical-chemical and biological parameters at points of user confluence. The results show that 78.78% of the total area of the basin is composed of primary vegetation and that the right margin showed the greatest change in its natural aspects. For the Multiple Uses of Water Resources, the space unit comprises, in the high course, activities of exploration of sand, domestic use, bus for agriculture and pisciculture; in the low Puraquequara, the uses were public supply, navigation, school transport, bovine industry, naval industry and subsistence agriculture. In the evaluation of the water quality, the areas of confluence investigated showed, respectively, for Water Quality Index (IQA), good, optimum, regular and optimal results, in the points Igarapé do Boa Vista, Igarapé do Mainã, German Refrigerator and Shipyard DMN. Thus, the Puraquequara River basin presented positive results for the indicators evaluated, but the monitoring of Land Use and Coverage, expansion of water uses and especially its quality should continue, since its studies subsidize the Planning and Management of Water Resources and alert social actors who enjoy their space.